Exploring undergraduate students’ general attitudes towards Artificial Intelligence: A perspective from Vietnam - Tien Le Minh (Journal of Language and Cultural Education)
Undergraduate students’ attitudes towards Artificial Intelligence (AI) in developing countries like Vietnam are rarely explored despite AI’s increasing presence in higher education. This study aims to investigate the attitudes of undergraduate students towards AI. A quantitative research method was used, involving a self-reported survey questionnaire. The sample consisted of 460 undergraduate students (196 males and 264 females) from five public and private universities in Ho Chi Minh City, Vietnam. Data collection took place through a cross-sectional survey in November and December 2023. The General Attitudes Towards Artificial Intelligence Scale (GAAIS), originally developed and validated in English by Schepman and Rodway (2020), was adapted to Vietnamese for this study. The scale comprised 20 items to evaluate students’ attitudes towards AI. Data analysis included descriptive statistics, Cronbach’s alpha coefficient, t-tests, and one-way Analysis of Variance (ANOVA). The results indicated a Cronbach’s Alpha value of 0.705 for the total variable, demonstrating acceptable reliability. Consequently, Vietnamese undergraduate students displayed moderately positive attitudes towards AI. The findings also revealed no significant difference in attitudes based on gender, but there was a notable variation based on the student’s year of study at university.